FMA Roundtable on New Developments in European Corporate Governance. Issue 1 (6th April 2017) - Elson, Charles; Berglund, Tom; Rapp, Marc Steffen; Bessler, Wolfgang; Chew, Don
Abstract : In this discussion that took place in Helsinki last June, three European financial economists and a leading authority on U.S. corporate governance consider the relative strengths and weaknesses of the world's two main corporate financing and governance systems: the Anglo‐American market‐based system, with its dispersed share ownership, lots of takeovers, and an otherwise vigorous market for corporate control; and the relationship‐based, or "main bank, " system associated with Japan, Germany, and continental Europe generally. The distinguishing features of the relationship‐based system are large controlling shareholders, including the main banks themselves, and few takeovers or other signs of a well‐functioning corporate control market. Given the steady increase in the globalization of business and international diversification by large institutional investors, the panelists were asked to address the question: can we expect one of these two systems to prevail over time, or will both systems continue to coexist, while seeking to adopt some of the most valuable aspects of the other? The consensus was that, in Germany as well as continental Europe, corporate financing and governance practices have already begun to look much like those in the U.S. and U.K., with much less reliance on bank loans and greater use of bonds and public equity. And these financing changes have resulted in major changes in ownership structures that have seen local main banks largely supplanted by foreign institutional investors—some of whom have demanded a greater voice in how companies are run. Moreover, Finnish economist Tom Berglund may well have provided a blueprint for the dominant European governance system of the future in describing the "Nordic model" as a compromise between the Anglo‐American and German models—one that maintains a strict hierarchy of interests putting the shareholders at the top, with strong minority shareholder protection, and gives shareholders the right to convene meetings with the board and executive management . But even with this movement toward the market‐based system, the remarkable persistence of family‐controlled publicly traded companies in Germany and much of continental Europe appears to reflect deep‐seated cultural attitudes and practices that are expected to continue to resist the incursion of Anglo‐American principles and methods. The widespread use of dual‐class stock, the pervasiveness of stateowned enterprises, and even the German practice of labor representation on boards (known as "codetermination") are all seen as likely to persist—even though one member of the panel views each of these three practices as having played a major role in the Volkswagen emissions scandal. And given the surprising resurgence of one of these features in the U.S.—that is, the dual‐class ownership structures created by the IPOs of companies like Google and Facebook—no one was confident in predicting their disappearance. Like many of today's listed German companies that have been owned and operated by the same family for centuries, some of America's most promising and successful companies also appear to feel the need for at least some protection against the "vagaries" of the market.